Language, Culture, and Identity - Wisconsin Center for Educational Research, Madison. National Center for Effective Schools; Wisconsin Center for Educational Research, Madison. National Center for Effective Schools ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1994)
This theme issue, devoted to the relationship between language, culture, and identity, contains three articles, all by Anne Turnbaugh Lockwood, and a commentary by Florence L. Johnson. The first article, entitled "The Heart of Culture," reports on an interview with Henry T. Trueba, an educator specializing in the roles of language, culture, and identity in the schooling of language minority children. In it, the experience of immigrants in a new society is examined and the ideal bilingual education experience is discussed. "Coming to America" profiles a Mexican immigrant boy who grows to manhood in the United States and copes successfully with the challenges of maintaining his native language and learning and new language and culture, and then became an elementary school teacher."Language, Culture, and Education" presents the story of one elementary school teaching an increasingly diverse student population, using creative solutions to difficult challenges. Florence Johnson's commentary and review of literature focuses on three concerns about schooling in the United States: (1) how teachers' perceptions, expectations, and educational practices are influences by children's race, culture, language, and social class; (2) the effects of these on student outcomes; and (3) what schools can do to create positive experiences for children. (MSE)
Focus in Change, n14 Spr 1994.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Standards; Acculturation; Curriculum Design; Elementary Secondary Education; English (Second Language); Immigrants; Language Maintenance; Language Role; Limited English Speaking; Minority Groups; Collected Works, Serials